Alternative perspectives on Mild Cognitive Impairment (MCI): Broadening the definition of MCI. - Gaviria, Moises (2012)
Mild cognitive impairment (MCI) is a relatively newly described phenomenon representing a mild deficit on the continuum between normal aging and dementia. Although MCI is the source of much interest and research in the fields of neuroscience and medicine, its definition, prevalence, and criteria for diagnosis has yet to become standardized and is the subject of much controversy. While there is some consensus among American and European researchers about the construct of MCI, others argue that these researchers focus too much on MCI as a preclinical state of Alzheimer’s disease (Ad) and thus is too narrow. MCI must also be examined in the context of each individual patient, taking into account each person’s unique needs and the degree to which his or her life is affected by the cognitive impairment in question. As the upcoming DSM-5 criteria are still being decided, it is a particularly opportune time to focus on alternative perspectives and definitions of MCI to ensure the best clinical definition possible can be determined.